Políticas educacionais, currículo e Educação Física no Instituto Federal da Paraíba - Santos, Samara Celestino dos (2025)
This study addresses Educational Policies, particularly the National Common Curricular Base (BNCC) and the High School Reform (REM), within the context of High School at the Federal Institute of Education, Science, and Technology of Paraíba (IFPB). The thesis argues that the implementation of REM and BNCC influences the Physical Education (PE) curriculum, producing changes that affect students’ holistic education, such as curricular flexibilization, reduction of PE class hours and, consequently, teaching workload, contributing to the delegitimization of the subject within the educational context. The general objective of the research was to understand how the implementation of BNCC and REM impacted the PE curriculum component at IFPB. With a qualitative-quantitative, descriptive, and exploratory approach, the investigation sought to analyze how such policies affect the Integrated High School Program, based on normative documents and the perceptions of PE teachers. For data production, the BNCC for High School, Laws nº 13.415/2017 and nº 14.945/2024, and Pedagogical Course Projects were used, along with semi-structured interviews with teachers from participating campuses. Document analysis was conducted through Thematic Analysis, and the interviews were examined using Semantic Network Analysis and Social Network Analysis. Data were processed using Python software (networkx package) and Gephi 0.10.1, applying the ForceAtlas2 algorithm. The results indicated that the PPCs share similar structures but were developed in different years, the most recent being five years old. The distribution of PE workload is not uniform across campuses, since each has autonomy to define it. Although a reduction was observed in some cases, this does not appear to stem from BNCC or REM, as the weekly load of 2 to 3 hours per week still predominates. The syllabi are not standardized but address the body culture of human movement, relating body, health, leisure, and the world of work. The content is diverse but continues to emphasize physical exercise, sports, and health. Assessment is described as continuous but is also based on technical performance and attendance. The concept of an integrated curriculum aligned with Professional and Technological Education is not contemplated in the PPCs, standing in disagreement with the Institutional Development Plan. Based on the analysis of the documents, Physical Education did not experience direct repercussions from the BNCC or the High School Reform, as they were not implemented within the context of the IFPB. Teachers narratives confirmed the absence of impact and revealed a lack of knowledge or only superficial understanding of the documents, which were often confused with one another. In conclusion, the study argues that the problems of Brazilian education are not centered on the curriculum itself, but rather on neoliberal educational policies that govern systems, negotiate education, and shape teaching processes. It reinforces the need to defend the quality and relevance of Federal Institutes. Furthermore, Law nº 14.945/2024 is not recognized as progressive, since it maintains the logic of skills and competencies, formative itineraries, and curricular flexibilization, thereby preserving the essence of neoliberal educational policies.